COMBINED EFFECT OF BIOCHAR RESIDUE AND FERTILIZER APPLICATION ON MAIZE GROWTH AND PRODUCTION IN LAMPUNG ULTISOL - Afriliyanti, Rizki; Yusnaini, Sri; Septiana, Liska Mutiara; Hidayat, Kuswanta Futas; Tama, Anggryta Widia (Jurnal Agrotek Tropika, 2025)
This study aimed to evaluate the combined effect of biochar residue and fertilizer application on the growth and production of maize (Zea mays L.) in Lampung Ultisol. The research was conducted at the Integrated Field Experiment, Faculty of Agriculture, University of Lampung. A factorial experiment was arranged in a Randomized Complete Block Design (RCBD) with two factors. The first factor was soil amendment residue treatments (B), consisting of B0: no soil amendment residue, B1: rice husk biochar residue 5 tons ha⁻¹ + cattle manure residue 5 tons ha⁻¹, B2: maize cob biochar residue 5 tons ha⁻¹ + cattle manure residue 5 tons ha⁻¹, and B3: cassava stem biochar residue 5 tons ha⁻¹ + cattle manure residue 5 tons ha⁻¹. The second factor was the application rate of N, P, and K fertilizers, comprising P0: no fertilizer (Urea 0 kg ha⁻¹, TSP 0 kg ha⁻¹, and KCl 0 kg ha⁻¹), P1: ½ recommended fertilizer dose (Urea 225 kg ha⁻¹, TSP 112.5 kg ha⁻¹, and KCl 100 kg ha⁻¹), and P2: full recommended fertilizer dose (Urea 450 kg ha⁻¹, TSP 112.5 kg ha⁻¹, and KCl 100 kg ha⁻¹). A total of 12 treatment combinations were tested and replicated three times. The results showed that fertilizer application significantly affected most maize growth and yield parameters, including plant height, stem diameter, leaf number, and grain yield. Soil amendment residue, particularly maize cob biochar combined with manure (B2), positively influenced vegetative growth but had a less consistent impact on yield components. No significant interaction was found between biochar residue and fertilizer application for most variables. These findings suggest that while fertilizer application plays a crucial role in improving maize productivity in Ultisol soils, the addition of biochar residues can enhance plant growth, potentially contributing to long-term soil fertility improvement.